EFFECTS OF MALNUTRITION AND IMPROPER CAPTIVE MAINTENANCE ON EUROPEAN POND TURTLE (EMYS ORBICULARIS): A CASE REPORT - L. B. Köbölkuti; G. Á. Czirják; M. Spînu (Journal of Animal and Plant Sciences, 2016)
The European pond turtle (Emys orbicularis), the most widely distributed European aquatic turtle species, although is protected in most countries under national and international laws, it is also kept in captivity as pet or as part of different conservation programs. Despite these circumstances, there is little to no information on the diseases affecting this species, especially on how certain captivity conditions contribute to these pathologies. Here we describe the effects of improper husbandry conditions on a European pond turtle (E. orbicularis) male. The animal was kept exclusively onsolid ground and fed with vegetables as would be a terrestrial species, which led to chronic malnutrition, dehydration and stress, and subsequently to the overgrowth of the beak and nails, lameness and secondary stomatitis associated with Candida spp. and Aeromonas hydrophila. The corrections of husbandry conditions combined with an adequate antimicrobial therapy resulted in full recovery and subsequent release of the turtle. Besides reporting a new case in a European reptile species, we would like to emphasize the role of veterinarians in notifying the owners about correct husbandry conditions for different reptile species and about the conservation and legal aspects of keeping protected indigenous species.
Keywords: Aeromonas hydrophila; beak overgrowth; Candida spp.; captivity; Emys orbicularis; infectious stomatitis; improper husbandry; lameness